The Character Development of Suzuko in One Million Yen Girl movie: A Descriptive Qualitative Study on Characterization and Social Representation - Rayza Aulya Nahari; Otong Setiawan Djuharie (INDO PUBLISHING, 2025)
This study aims to analyze the character development of the main protagonist, Suzuko, in the film One Million Yen Girl directed by Yuki Tanada. The focus of the research is on how Suzuko's character is constructed and evolves through key scenes and dialogues that reflect her personal struggle against social stigma and her quest for freedom. The method used is descriptive qualitative, employing purposive sampling to select 15 key scenes that represent Suzuko's character transformation. The data are analyzed in depth to describe the physical, psychological, and social aspects of Suzuko's character as well as her emotional development throughout the film. The results show that Suzuko evolves from a closed and pressured individual into an independent, strong person who gradually opens herself to others. Suzuko’s life journey, full of conflicts and struggles, mirrors a realistic and complex character change. This study contributes to the field of film character analysis and enriches the understanding of social representation in audiovisual art works.